Pathogenetic, Clinical, and Prognostic Features of Adult t(4;11)(q21;q23)/MLL-AF4 Positive B-Cell Acute Lymphoblastic Leukemia - F. Marchesi; K. Girardi; G. Avvisati (Advances in Hematology)
Translocation t(4;11)(q21;q23) leading to formation of MLL-AF4 fusion gene is found in about 10% of newly diagnosed B-cell acute lymphoblastic leukemia (ALL) in adult patients. Patients expressing this chromosomal aberration present typical biological, immunophenotypic, and clinical features. This form of leukemia is universally recognized as high-risk leukemia and treatment intensification with allogeneic hematopoietic stem cell transplantation (HSCT) in first complete remission (CR) could be a valid option to improve prognosis, but data obtained from the literature are controversial. In this review, we briefly describe pathogenetic, clinical, and prognostic characteristics of adult t(4;11)(q21;q23)/MLL-AF4 positive ALL and provide a review of the clinical outcome reported by the most important cooperative groups worldwide.